Unmet need in family planning at the Cape Coast Teaching Hospital of Ghana - Azize, Diallo Abdoul; Evans, Ekanem; Frederick, Agyare-Gyan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Knowing the prevalence of unintended pregnancy, unmet need in family planning and the associated factors in cape coast, is important for ensuring that all women have access to the most effective methods of family planning in order to reduce the occurrence of unintended pregnancies. This study aims to determine the prevalence of unintended pregnancies, unmet need in family planning and the associated factors among women attending antenatal clinics at the Cape Coast Teaching Hospital, Republic of Ghana. Methods: A prospective cross-sectional study with descriptive and analytical components was carried out from 20th April 2015 to 20th June 2015 to simultaneously measure the prevalence of unmet need for family planning and related factors. All clients reporting for ANC at the Cape Coast Teaching Hospital during the study period were recruited into the study. Results: A total of 324 clients were recruited. The mean age was 29.98±5.86 years, 85.80% were married, 46.58% had tertiary education and 79.94% had a source of income. Up to 54.94% of the clients had not planned their index pregnancy. Among subjects who had not planned their index pregnancies, 74.71% had not used a family planning method. There is a significant association between age, educational level, the presence of a source of income, marital status and the occurrence of unplanned pregnancy. Conclusions: There were high prevalence of unplanned pregnancy and unmet need for family planning. There is a significant association between age, educational level, the presence of a source of income, marital status and the occurrence of unplanned pregnancy.